Analisis Potensi Penurunan Muka Air Tanah di Salah Satu Bandar Udara Jawa Timur - Yusuf Ardiansyah; Hikmah Ayu Murti (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Nowadays, groundwater in the world has been widely exploited along with the increasing population. One of the impacts of massive groundwater extraction is the decline in groundwater levels. This potential could occur at one of the airports in East Java which is one of the most crowded airports in Indonesia. The large number of passengers at the airport has increased groundwater extraction due to the increasing need for sanitation, airport facilities, and other operational needs. This study aims to determine the potential for groundwater level decline at one of the airports in East Java. The research method used is a quantitative method by projecting secondary data from the results of groundwater level sampling carried out every 6 months. The results of the study showed a decline in groundwater levels at one of the airports in East Java in the next 20 years due to the increase in passengers each year. The results of this study are expected to be one of the preventive steps for all of us to maintain the sustainability of groundwater resources.